Slovenski pogled na spiritizem v dobi meščanstva - Perovšek, Jurij (Prispevki za novejšo zgodovino, 2024)
During the bourgeois era in Slovenia, a lot was written about spiritualism, its appearance, development, and characteristics. Many lectures were given, and the literature about it, published throughout the world, was followed closely. It was well known in Slovenia, and a cross-section of the contemporaneous society and politics reveals that the general opinion about it was mostly disapproving and derisive. It was perceived as superstition, deception, a sign of psychological depravity, phantasmagoria, unproven phenomena, blind faith, and as simply wrong. Catholic authors characterised it as contrary to religion and hostile to humanity and God. The liberals believed that people resorted to spiritualism because of social hardships, while the communists saw it as a dangerous poison for the working people, which could undermine their class consciousness. Spiritualism was most favoured in the mining areas.
Keywords: bourgeois age; doba meščanstva; mining areas; negative valuation; negativno vrednotenje; rudarski revirji; slovenski pogled; spiritizem; spiritualism; the Slovenian outlook